Organizational Learning Strategies in The Management of Educational Institutions: A Bibliometric Review in Scopus - Alfaro-Rosas, Marita Marleni; Merino-Salazar, Teresita del Rosario; Cardoza-Sernaqué, Lizbany Sujey; Salinas-Ruíz, Henry Eduardo; Chero-Valdivieso, Henry Alberto; García-Ventura, Cynthia Catherine; Saldaña-Millan, Jackeline Margot (International Journal of Membrane Science and Technology, 2023)
The objective of this study was to carry out a review to know the state of the literature on organizational learning strategies in the management of educational institutions in the Scopus database. The methodology used was the bibliometric review, seeking to quantify. On this occasion he came up with the total of subsequent publications in Scopus. Resulting in a total of 14 publications after their identification, they were analyzed using CRAN-R and Bibliometrix. 2017 has been the year with the greatest impact at the total level of citations for studies; it was identified that the most frequent keyword was "organizational learning". Regarding the author with the most frequent use of keywords, it was Lewis MM. The most frequently published source of studies was Springer Science+Business (n=2). The author analysis identifies Fauske JR (TCpY= 1.421) and Eikeland O (TCpY= 0.909), suggesting the importance of both studies in related scientific production. Regarding the local impact indices, the h and G index were equal to 1, while the M index was higher for Herrera-Caballero JM with a value of 0.333. The most frequent affiliation among the studies was the Metropolitan Technological Institute. According to the scientific production by country, it is led by the United States (n=4). Finally, the author with the highest general citation is Sutano EM.